Evolution of a Record-Setting AT-Rich Genome: Indel Mutation, Recombination, and Substitution Bias. (28th September 2020) - Nguyen, Duong T; Wu, Baojun; Xiao, Shujie; Hao, Weilong
Abstract: Genome-wide nucleotide composition varies widely among species. Despite extensive research, the source of genome-wide nucleotide composition diversity remains elusive. Yeast mitochondrial genomes (mitogenomes) are highly A + T rich, and they provide a unique opportunity to study the evolution of AT-biased landscape. In this study, we sequenced ten complete mitogenomes of the Saccharomycodes ludwigii yeast with 8% G + C content, the lowest genome-wide %(G + C) in all published genomes to date. The S. ludwigii mitogenomes have high densities of short tandem repeats but severely underrepresented mononucleotide repeats. Comparative population genomics of these record-setting A + T-rich genomes shows dynamic indel mutations and strong mutation bias toward A/T. Indel mutations play a greater role in genomic variation among very closely related strains than nucleotide substitutions. Indels have resulted in presence–absence polymorphism of tRNA Arg (ACG) among S. ludwigii mitogenomes. Interestingly, these mitogenomes have undergone recombination, a genetic process that can increase G + C content by GC-biased gene conversion. Finally, the expected equilibrium G + C content under mutation pressure alone is higher than observed G + C content, suggesting existence of mechanisms other than AT-biased mutation operating to increase A/T. Together, our findings shed new lights on mechanisms driving extremely AT-rich genomes.